Analisis Perilaku Persalinan Komunitas Adat Terpencil di Wilayah Taman Nasional Bukit Duabelas Kabupaten Sarolangun Provinsi Jambi - guspianto guspianto; Andy Amir; Arnild Augina Mekarisce (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
The Remote Indigenous Communities (RIC) live in groups in the secondary forests of Jambi Province.The relatively primitive social, economic, cultural and environmental conditions cause RIC to have vulnerablebehavior towards health problems, including childbirth. This study aims to analyze the childbirth behavior inRIC who is considered to be a high risk of complications. The study design is descriptive qualitative research tounderstand holistically social phenomena about childbirth behavior among RIC in the Bukit Duabelas NationalPark area at Sarolangun Regency-Jambi. Research informants were selected purposively including Mothers whohad given birth, Husbands, Traditional Birth Attendants (TBAs), Tumenggung, and Midwives. This study foundin general childbirth behavior of RIC was unsafe and had a high risk that could have an impact on maternal andinfant mortality. This is likely influenced by the lack of knowledge, less supportive attitude, low of need perception,and health services have not been optimal. Living in scattered groups and habits of “melangun” are obstacles forproviding health services. It is recommended to improve the implementation of the P4K program and integratedhealth service activities, create a maternity shelter, provide “RIC Care Mobile”, and approach with RIC communityleaders (Tumenggung), and TBAs on the importance of safe delivery to maintain maternal health and safety.